Identification and validation of a major QTL on chromosome 2A for wheat-Parastagonospora nodorum interactions - Li, Cong; He, Xinyao; Ma, Jian; Singh, Pawan (BMC, 2025)
Wheat (Triticum aestivum L.) is frequently affected by Septoria nodorum blotch (SNB), a fungal disease that significantly reduces wheat yields. In this study, two recombinant inbred line (RIL) populations, developed from crosses involving two elite CIMMYT breeding lines (WUYA and KATH) and a common susceptible male parent (CIANO T79), were used to detect quantitative trait loci (QTL) associated with SNB resistance. High-density genetic maps were constructed for these RIL populations by incorporating presence/absence variation (PAV) markers using the DArTseq genotyping platform. Three major and stable QTL linked to SNB resistance were identified on chromosomes 2A, 4B, and 5B. Among these, QSnb.cim-2A accounted for 22.16%–28.74% and 17.62%–19.71% of the phenotypic variation in the WUYA/CIANO T79 and KATH/CIANO T79 populations, respectively, and it was also validated in the CASCABEL/CIANO T79 RIL population. The remaining two QTL, QSnb.cim-4B and QSnb.cim-5B, were found to be associated with Rht-B1b and tsn1, respectively. The combined effect of these three QTL significantly improved SNB resistance while also reducing plant height, indicating their promising utilization in wheat breeding programs.